The Influence of Auxin and Ethylene on Chromatin-directed Ribonucleic Acid Synthesis in Soybean Hypocotyl - Holm, Robert E. (1970)
Soybean seedlings treated with ethylene exhibited small increases in ribonucleic acid content in the elongating section of the hypocotyl. Chromatin isolated from the elongating section of ethylene-treated seedlings showed a 35 to 60% increase in the capacity for RNA synthesis. The ethylene-induced response was saturated at 1 microliter/liter of ethylene and was fully expressed after 3 hours. Auxin caused marked accumulation of RNA and DNA in the elongating and basal tissue of the hypocotyl. Chromatin isolated from these auxin-treated tissues showed an 8- to 10- fold increase in RNA synthetic capacity as measured in vitro. Ethylene added with auxin reduced the auxin enhancement of nucleic acid synthesis in the elongating and basal tissues. Both ethylene and auxin treatment of the seedlings inhibited nucleic acid accumulation and chromatin activity in the apical tissue. Ethylene did not appear to mediate the auxin effects on nucleic acid synthesis in soybean hypocotyl with the possible exception of inhibition in the apical tissue. The RNA which was synthesized by chromatin isolated from control and auxin- and ethylene-treated tissues was characterized by nearest neighbor analyses. The nearest neighbor frequencies of the RNA products synthesized by chromatin isolated from auxin- and ethylene-treated hypocotyl tissue were different from each other and different from the control RNA product. Seedlings treated in sealed containers exhibited growth, RNA, and DNA responses, especially to ethylene, different from those of seedlings treated in continuous flow containers.